PENGARUH PENERAPAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA KELAS V MI PADA PEMBELAJARAN IPS - Sa’diyah, Maemunah; Aqliyah, Ismania Nur; Marasabessy, Yusra (ATTA`DIB, 2016)
This research aims to know the effect of application of role playing method toward student’s learning outcome at class V MI Al Madani on social science. In this research, the researcher conducted descriptive-quantitative method which is experimental research. The population is the whole students, and the sample is class V A 23 students as experiment class and class V B 23 students as control class. The data was analyzed by observation, documentary and multiple choice test and essay. The result of the research shows that there is difference significantly on their learning outcome between experiment class and control one. The role playing method affects the students’ learning outcome on social science. It can be seen from their average of their post test. They achieved 74,78 in experiment class and 65.56 in control class. This shows that application of role playing method gives an effect to the students’ learning outcome at MI Al Madani Bogor.